2014
DOI: 10.1016/j.ejenta.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Lobular capillary hemangioma of the nasal septum – A case report

Abstract: Lobular capillary hemangioma is a benign, rapidly growing lesion of the skin and mucous membranes. It may rarely present as a mass that entirely fill the nasal cavity with an unknown etiology. Although it has no predilection for age, it is more common in the third decade and in females. Lobular capillary hemangioma usually involves the gingiva, lips, tongue, and buccal mucosa. The nasal cavity is a rare location. The most common symptoms are nasal obstruction and epistaxis. The treatment is nasal endoscopic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Patrice et al reported a series of 178 patients with LCH. Seventy-four per cent of their cases had no history of trauma [10].In our patients, none of these potential etiological factors were present, it is consistent with another report [11].It should be noted that contrast enhanced MRI is the preferred method for imaging, although CT scan can also be considered if MRI is not available. Furthermore CT scan may demonstrate bony expansion or erosion [12].…”
Section: Discussionsupporting
confidence: 90%
“…Patrice et al reported a series of 178 patients with LCH. Seventy-four per cent of their cases had no history of trauma [10].In our patients, none of these potential etiological factors were present, it is consistent with another report [11].It should be noted that contrast enhanced MRI is the preferred method for imaging, although CT scan can also be considered if MRI is not available. Furthermore CT scan may demonstrate bony expansion or erosion [12].…”
Section: Discussionsupporting
confidence: 90%
“…It was first described by Poncet and Dor in 1897 as botryomycosis hominis based on the assumption that it arose secondary to a fungal infection [ 6 ]. Because it has since been shown to be neither infectious nor granulomatous, the term pyogenic granuloma is now considered a misnomer [ 2 , 3 ]. Based on its histopathological features, the name LCH was assigned to these tumors by Miller [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grossly, it appears as a polypoidal mass with an ulcerated surface that is covered with fibrin and blood [ 7 ]. Microscopically, it is further characterized by an association with numerous capillary sized blood vessels featuring edematous and inflamed stroma [ 2 4 , 7 ]. LCH can be either pedunculated, meaning that it has a stalk that attaches the mass to its site of origin, or it can be sessile, meaning that the mass is fixed to its base without any peduncles [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations